Multidecadal Seesaw in Hadley Circulation Strength Between the Two Hemispheres Caused by the Atlantic Multidecadal Variability - Liu, Yusen; Gong, Zhanqiu; Sun, Cheng; Li, Jianping; Wang, Lin (Frontiers in Earth Science, 2020)
Multidecadal variations in Hadley circulation (HC) strength have been observed during the historical period, which have significant implications for global and regional climate. However, the relationship between HC intensities in the two hemispheres remains unclear. In this study, we identify an interhemispheric seesaw in the annual HC strength at multidecadal timescales. This seesaw pattern physically corresponds to the meridional movement of the ascending branch of annual HC, leading to strengthened HC in one hemisphere and weakened HC in the other. The HC strength seesaw strongly correlates with the tropical land surface precipitation at multidecadal timescales, particularly for the monsoonal land regions. Further analyses link the HC strength seesaw to the Atlantic multidecadal variability (AMV). A suite of Atlantic Pacemaker experiments successfully reproduces the multidecadal HC strength seesaw and its relation to the AMV. The Northern Hemisphere SST warming associated with the positive AMV phase induces a northward shift of the upward branch of HC, and the Southern Hemispheric HC is strengthened in contrast to the weakened Northern Hemispheric HC. Comparisons of the North Atlantic SST forced HC changes between the coupled air–sea model and stand-alone atmospheric model suggest an important and non-negligible role of the SST footprint of AMV over the Indo-Pacific basins. The AMV and its Indo-Pacific SST footprint make a comparable contribution to the SST changes in the Northern Hemisphere, which control the movement of the HC ascending branch and thereby the interhemispheric seesaw in HC strength.